The Other Side of the Trade‐Off: The Impact of Risk on Executive Compensation - Aggarwal, Rajesh K.; Samwick, Andrew A. (Journal of Political Economy, 1999)
The principal‐agent model of executive compensation is of central importance to the modern theory of the firm and corporate governance, yet the exiting empirical evidence supporting it is quite weak. The key prediction of the model is that the executive's pay‐performance. We demonstrate strong empirical confirmation of this prediction using a comprehensive sample of executives at large corporations. In general, the pay‐performance sensitivity for executives at firms with the least volatile stock prices is an order of magnitude greater than the pay‐performance sensitivity for executives at firms with the least volatile stock prices. This result holds for both chief executive officers and other highly compensated executives. We further show that estimates of the pay‐performance sensitivity that do not explicity account for the effect of the variance of firm performance are baised toward zero. We also test for relative performance evaluation of executives against the performance evaluation model. Our findings suggest that executive compensation contracts incorporate the benefits of risk sharing but do not incorporate the potential informational advantages of relative performance evaluation.